agCelerant selected as technical implementation partner for the Regional Rice Value Chain Program (RRVCP) - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
Selected by IsDB under the RRVCP, agCelerant will provide a de-risking solutions and a vehicle for agricultural credit and phygital monitoring of its use by 2 million rice growers